Photophysical studies of conjugates of upconversion nanoparticles with aluminium phthalocyanines - Watkins, Zane (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
NaYF4 :Yb/Er/Gd upconversion nanoparticles (UCNP) were synthesised and their photoemission stabilised by embedding these nanoparticles in electrospun fibres. The photophysical behaviour of chloro aluminium tetrasulfo-phthalocyanine chloride (ClAlTSPc) was studied in the presence of UCNPs on mixing the two species in solution. The fluorescence lifetimes for UCNPs were shortened at 658 nm in the presence of ClAlTSPc when the former was embedded in fibre and suspended in a dimethyl sulfoxide solution of the latter. A clear singlet oxygen generation by ClAlTSPc through Forster resonance energy transfer (FRET) was demonstrated using a singlet oxygen quencher, 1,3-diphenylisobenzofuran. UCNP capped with amino groups were then covalently attached to chloro aluminium tetrasulphonated phthalocyanine (ClAlTSPc) and chloro aluminium tetracarboxy phthalocyanine (ClAlTCPc). The conjugates were characterized using different techniques such as infrared spectroscopy (IR), X-ray photoelectron spectroscopy (XPS) and Transmission electron microscopy (TEM). There was a decrease in fluorescence emission spectra of the UCNPs at 658 nm in the presence of the phthalocyanines. This decrease indicates an energy transfer between the donor UCNP and conjugated accepting phthalocyanine (Pc), due to FRET. Low FRET efficiencies of 18 and 21 % for ClAlTSPc and ClAlTCPc, respectively, were obtained.
Keywords: Uncatalogued